Mental Violence: The COVID-19 Nightmare - Musse, Fernanda Cristina Coelho; Castro, Laura de Siqueira; Sousa, Ksdy Maiara Moura; Mestre, Thiago Fuentes; Teixeira, Camila De Masi; Pelloso, Sandra Marisa; Poyares, Dalva; Carvalho, Maria Dalva de Barros (Frontiers in Psychiatry, 2020)
The year 2020 has generated profound changes in personal and working relations, and in dreams of millions of people worldwide. The aim of this study was to investigate the frequency and content of nightmares during the COVID-19 pandemic in Brazil, evaluating its associations with sociodemographic, occupational, and clinical factors. Cross-sectional exploratory study, including 1,057 participants who responded to an online survey about mental violence and nightmares during the pandemic, between May 25 and June 1, 2020. A descriptive analysis of the results was done to obtain frequency tables. McNemar's nonparametric test was used to compare the frequency of nightmares before and after the pandemic, and logistic regression models, to identify factors most strongly associated with the pandemic nightmares. Participants were from 21 Brazilian states, with a mean age of 38±14 years, and 78% women. Half of them (n=529) reported at least one nightmare episode during the pandemic, and 32.9% (n=348) described a pandemic content. There was nearly a 3-fold increase in the occurrence of nightmares “once a week or more” during the pandemic, 9% before versus 25% after. Prior psychiatric care, suicidal ideation, sleep medication, increased pandemic alcohol consumption, perceiving high risk of contamination, being woman, and of younger age were factors associated with having nightmares during the pandemic. Prior psychiatric care, sleep medication, and age remained significant after excluding participants without nightmares and comparing between individuals with and without a pandemic content. We conclude the COVID-19 pandemic has affected people's dreams. The increase in the frequency of nightmares, their pandemic content, and association with previous conditions are a concerning public mental health issue and should be taken into consideration by authorities and policy makers.